1991
DOI: 10.2116/analsci.7.573
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Diamino- and Aminopyrenes by High Performance Liquid Chromatography with Chemiluminescence Detection

Abstract: A high performance liquid chromatographic (HPLC) method with chemiluminescence (CL) detection was developed for the sensitive determination of 1,3-diaminopyrene (1,3-DAP), 1,6-DAP, 1,8-DAP and 1-aminopyrene (1-AP). The HPLC conditions were as follows: column, Cosmosil 5C18 (4.6 mm i.d.X250 mm); mobile phase, 10 mM imidazoleperchloric acid buffer(pH 7.6)-acetonitrile (1:1, v/v); CL reagent, 0.02 mM bis(2,4,6-trichlorophenyl)oxalate (TCPO) and 15 mM hydrogen peroxide in acetonitrile. The oxidative degradation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 17 publications
(1 reference statement)
0
38
0
Order By: Relevance
“…16,29,30,32 Recently, a combination of hydrazine and Raney nickel catalyst was used to reduce 3-NBA. 26 In the experiment, NBA isomers were reduced by Pt/Rh catalyst.…”
Section: Reduction Of Npahsmentioning
confidence: 99%
“…16,29,30,32 Recently, a combination of hydrazine and Raney nickel catalyst was used to reduce 3-NBA. 26 In the experiment, NBA isomers were reduced by Pt/Rh catalyst.…”
Section: Reduction Of Npahsmentioning
confidence: 99%
“…Table 2 shows the detection limit of the present method, together with those of the conventional methods such as fluorescence9 and CL methods. 6 The present method thus improved substantially the sensitivity for the determination of DNP.…”
Section: Metal Free Hplc Systemmentioning
confidence: 71%
“…5. The use of ascorbic acid has been proposed for the improvement of CL stability by Hayakawa et al 6 System A showed a small CL intensity without any peak separation. Although System B has much improved the intensity and has achieved resolution of three peaks, a negative peak due to ascorbic acid was observed, resulting in distortion of the baseline.…”
Section: Metal Free Hplc Systemmentioning
confidence: 99%
“…The solution was filtered with a 0.45 μm HLC-Disk membrane filter (Kanto Chemical Co., Inc., Tokyo, Japan), and an aliquot of this solution was injected into the HPLC system for NPAHs. Other conditions were the same as in our previous reports (Tang et al, 2002a;Hayakawa et al, 1991).…”
Section: Analytical Procedures and Qualitymentioning
confidence: 98%